Retail market structure and consumer prices in the euro area - Emanuela Ciapanna; Concetta Rondinelli (European Central Bank (ECB), 2014)
We investigate the empirical relationship between product market competition and prices in the retail grocery sector in the euro area. The study uses micro-data from ACNielsen on chain stores' census characteristics and price levels for a broad variety of products. We construct Herfindahl-Hirschman indices of concentration at different levels of market aggregation (buying group and parent company) to investigate their effects on prices. The analysis confirms the inverse relation between downstream market competition among retailers and price levels for most of the reference products. Though less conclusive in terms of statistical significance, the proposed estimates also point to a welfare enhancing role of buying groups. Our results indicate that buying groups provide a balancing mechanism between retailers' and producers' bargaining power, in support of the countervailing power hypothesis.
Keywords: L1; L4; L8; E31; 330; buying group; market concentration; parent company; price levels; regional Herfindahl-Hirschman indices